Princípios éticos na experimentação animal - Marona, H. R N [UNESP] (My University, 2004)
The treatment of animals used in research or in education tests requires proper care, scientific judgment and qualified professionals to understand the needs of the animals and the special requirements of the research, tests, and educational programs. The established guidelines aim the development of knowledge necessary for the improvement of health and wellbeing of humans as well as animals to get precise and accurate results. The techniques should not be performed with inappropriate procedures that cause pain or suffering. Some principles should be considered to have an appropriate animal care and treatment.
Ethical principles in the animal experimentation
Keywords: Animal welfare; Ethics; In vivo assay; animal care; animal experiment; animal wellbeing; education; ethics; experimental animal welfare; nonhuman; practice guideline; review